TRANSFORMATION OF SCIENCE LEARNING: THE EFFECTIVENESS OF DIFFERENTIATED INSTRUCTION-BASED TEXTBOOKS IN IMPROVING SCIENCE LITERACY AND CURIOSITY IN BIOTECHNOLOGY - Mardiana Dewi; Insih Wilujeng (Universitas Bhinneka PGRI, 2026)
This study was motivated by low science literacy and declining inquiry motivation among students due to the limited availability of teaching materials that accommodate diverse learning readiness. The purpose of this research was to develop differentiated science textbooks on biotechnology and to examine their validity, practicality, and effectiveness in improving science literacy and curiosity among ninth-grade junior high school students. The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). The textbooks were designed based on learning readiness levels (basic, intermediate, and advanced) and integrated with Discovery Learning syntax. Data were collected through expert validation, teacher and student questionnaires, and effectiveness testing using a quasi-experimental design. Descriptive statistics and non-parametric inferential tests were applied for data analysis. The findings indicated that the developed textbooks demonstrated very high validity and practicality. Furthermore, students in the experimental group achieved significantly higher posttest scores in science literacy and curiosity compared to the control group. These results suggest that differentiated science textbooks are effective in supporting student-centered learning and enhancing both cognitive and affective outcomes.